Base excision repair initiated rolling circle amplification-based fluorescent assay for screening uracil-DNA glycosylase activity using Endo IV-assisted cleavage of AP probes. Issue 16 (12th July 2018) - Wang, Jingfeng; Wang, Yu; Liu, Su; Wang, Haiwang; Zhang, Xue; Song, Xiaolei; Huang, Jiadong
Abstract : A simple, robust and cost effective biosensing platform for the ultrasensitive detection of UDG activity was established based on base excision repair-initiated primer generation for RCA with Endo IV-assisted signal amplification. Abstract : Uracil-DNA glycosylase (UDG) is a crucial damage repair enzyme that initiates the cellular base excision repair pathway that maintains the integrity of the genome. Abnormal UDG activity may induce the malfunction of uracil excision repair that is directly related to a range of diseases including cancers, genotypic diseases, and human immunodeficiencies. In this work, a simple, robust and cost effective biosensing platform for the ultrasensitive detection of UDG activity is established based on the combination of base excision repair-initiated primer generation for rolling circular amplification (RCA) with Endo IV-assisted signal amplification. In the presence of target UDG, UDG can catalyze the removal of uracil on a hairpin probe (HP) leaving an apurinic/apyrimidinic (AP site) which can be cleaved by Endo IV to generate a primer for triggering the RCA reaction. Subsequently, numerous AP site-embedded signal probes, acting as fluorescence-quenched probes, combine with the RCA products to perform signal transduction and quadradic signal amplification through an Endo IV-catalyzed cleavage reaction, thus significantly enhancing the fluorescence signal, which can be used for UDG activity screening. Under optimum conditions, this biosensor exhibits improved sensitivity toward target UDG with a detection limit of as low as 9.3 × 10 −5 U mL −1 and a wide detection range across 5 orders of magnitude. Additionally, our biosensor demonstrates high selectivity toward UDG for simple, rapid, and low-cost detection. Furthermore, by redesigning the modification of HP and using of suitable endonuclease enzymes, this RCA coupled with Endo IV-assisted signal amplification strategy might be applied for the detection of various other targets, such as thymine DNA glycosylase, 8-oxoguanine DNA glycosylase, DNA methyltransferase, and so on. Hence, the proposed strategy provides a useful and versatile biosensing platform for the ultrasensitive detection of UDG activity and related fundamental biomedicine research and clinical diagnosis.